STUDY OF THE RATE OF MOISTURIZATION OF CLAY ROCKS - Salixova Ozada Abdullayeva; Ergasheva Dilfuza Amilovna (Academia Science Repository, 2023)
The technique is designed to test the stability of clay rocks of various degrees of lithification to the hydrating action of solutions that differ in qualitative and quantitative composition. The essence of the method for estimating the rate of wetting of clay samples is to exert point uniaxial pressure on a rock sample in the medium of the drilling fluid being tested. The technique is not applicable to clayey rocks containing large-clastic inclusions with a diameter of more than 3 mm that are not subject to hydration destruction, rocks with a high degree of moisture, as well as rocks in a frozen state.